Comparative profiling of well-defined copper reagents and precursors for the trifluoromethylation of aryl iodides - Kaplan, Peter T.; Lloyd, Jessica A.; Chin, Mason T.; Vicic, David A. (Beilstein Journal of Organic Chemistry, 2017)
A number of copper reagents were compared for their effectiveness in trifluoromethylating 4-iodobiphenyl, 4-iodotoluene, and 2-iodotoluene. Yields over time were plotted in order to refine our understanding of each reagent performance, identify any bottlenecks, and provide more insight into the rates of the reactions. Interestingly, differences in reactivity were observed when a well-defined [LCuCF3] complex was employed directly or generated in situ from precursors by published reports. Relative reactivities were also found to highly dependent on the nature of the iodoarenes.
Keywords: benchmarking; copper; fluorine; fluoroalkylation; trifluoromethylation